Peran Gaya Kepemimpinan Agile dalam Meningkatkan Kinerja Organisasi di Era Disrupsi Teknologi - Endah Budiyati; Meti Nurhayati; Erni Rihyanti (Yayasan Literasi Sains Indonesia, 2025)
The development of technology in the era of globalization now has a tremendous effect on human life. Various disruptions are presented by it. With these conditions, a person, especially as a leader, must follow the rapid changes presented by the development of globalization. Technological advances, for example, require a leader to adjust his leadership style to make quick decisions based on current conditions. This article wants to discuss the agile leadership style which is the answer to the style of a leader in the era of globalization. This article also uses a qualitative research method with data collection techniques from various references, such as books and journals. This article uses the concept of agile leadership which is the answer to the leadership style in the current era of globalization. This article argues that a leader with an agile leadership style becomes more adaptive to the development of globalization and has an impact on progress in the organization or company they lead to be achieved more quickly. This article concludes that the agile leadership style with its characteristics is the right answer for a leader in this era of globalization. Adaptation and calmness, for example, are important reasons for a leader in the current era of technological disruption.